2014
DOI: 10.1016/j.ymgme.2013.12.144
|View full text |Cite
|
Sign up to set email alerts
|

Altered dynamics of a lipid raft associated protein in a kidney model of Fabry disease

Abstract: Accumulation of globotriaosylceramide (Gb3) and other neutral glycosphingolipids with galactosyl residues is the hallmark of Fabry disease, a lysosomal storage disorder caused by deficiency of the enzyme alpha-galactosidase A (α-gal A). These lipids are incorporated into the plasma membrane and intracellular membranes, with a preference for lipid rafts. Disruption of raft mediated cell processes is implicated in the pathogenesis of several human diseases, but little is known about the effects of the accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…21 This is particularly interesting to understand the underlying disease mechanism and provide a cellular and molecular platform for developing novel treatment strategies. 22 In vitro cell models (Table 1), initially, used cells obtained from FD patients especially of target organs in FD: endothelial cells [23][24][25][26][27]29 kidney cells [48][49][50][52][53][54] to determine glycosphingolipids accumulation and a-Gal A activity, and obtain lines for further research. Fibroblast 32,34 and bone marrow cells 30,31 were subjected to different techniques to incorporate an a-Gal A for enzyme expression, as well as for the analysis of different mutations present in FD patients.…”
Section: Lenders Et Al 54mentioning
confidence: 99%
“…21 This is particularly interesting to understand the underlying disease mechanism and provide a cellular and molecular platform for developing novel treatment strategies. 22 In vitro cell models (Table 1), initially, used cells obtained from FD patients especially of target organs in FD: endothelial cells [23][24][25][26][27]29 kidney cells [48][49][50][52][53][54] to determine glycosphingolipids accumulation and a-Gal A activity, and obtain lines for further research. Fibroblast 32,34 and bone marrow cells 30,31 were subjected to different techniques to incorporate an a-Gal A for enzyme expression, as well as for the analysis of different mutations present in FD patients.…”
Section: Lenders Et Al 54mentioning
confidence: 99%
“…Such an example is found in a mouse model of Krabbe's disease, the twitcher mouse, in which toxic accumulation of galactosylsphingosine (psychosine) disrupts lipid rafts, resulting in the inhibition of survival signals such as PKC, Akt, and ERK; defects in axonal transport and synaptic maintenance; and neuronal degeneration through a dying‐back mechanism (White et al, ; Castelvetri et al, ; Cantuti Castelvetri et al, ; Hawkins‐Salsbury et al, ; Teixeira et al, ; Cantuti‐Castelvetri et al, ). Glucosylceramide accumulation in Gaucher's disease (Hattersley et al, ), sulfatide accumulation in metachromatic leukodystrophy (Moyano et al, ), globotriaosylceramide accumulation in Fabry's disease (Labilloy et al, ), and cholesterol accumulation in Niemann‐Pick type C (Vainio et al, ) also preferentially take place in lipid rafts and cause altered lipid raft dynamics. Therefore, it is conceivable that they involve neuronal vulnerability through a similar mechanism that includes membrane disruption as a root cause for downregulation of survival signals leading to neurodegeneration.…”
Section: Sphingolipids and Their Effect On Neuronal Survivalmentioning
confidence: 99%
“…N&B analysis was performed on wildtype and alpha-galactosidase deficient cells, which act as a model for Fabry's disease. Antibodyinduced clustering of a model lipid raft protein was increased in the mutant compared to control cells [110]. These results suggested that accumulated Gb3 may alter lipid raft protein interactions in membranes of alpha-galactosidase deficient cells.…”
Section: Examples Of Photodetector Used In Srm and Fftsmentioning
confidence: 77%
“…Hybrid detectors have been employed to measure the formation of lipid rafts in a cell model of Fabry's disease [110]. In Fabry's disease, lysosomal function is disrupted due to reduced activity of a specific enzyme (alpha-galactosidase A) that leads to accumulation of neutral glycosphingolipids such as globotriaosylceramide (Gb3).…”
Section: Examples Of Photodetector Used In Srm and Fftsmentioning
confidence: 99%